Functional Significance of Single Nucleotide Polymorphisms in the Lactase Gene in Diverse US Patients and Evidence for a Novel Lactase Persistence Allele at −13909 in Those of European Ancestry. Issue 2 (February 2015) - Baffour-Awuah, Nana Yaa; Fleet, Sarah; Montgomery, Robert K.; Baker, Susan S.; Butler, Johannah L.; Campbell, Catarina; Tischfield, Samuel; Mitchell, Paul D.; Allende-Richter, Sophie; Moon, Jennifer E.; Fishman, Laurie; Bousvaros, Athos; et al.
ABSTRACT: Objectives: Recent data from mainly homogeneous European and African populations implicate a 140-bp region 5′ to the transcriptional start site of LCT (the lactase gene) as a regulatory site for lactase persistence and nonpersistence. Because there are no studies of US nonhomogeneous populations, we performed genotype/phenotype analysis of the −13910 and −22018 LCT single nucleotide polymorphisms (SNPs) in New England children, mostly of European ancestry. Methods: Duodenal biopsies were processed for disaccharidase activities, RNA quantification by reverse transcription polymerase chain reaction (RT-PCR), allelic expression ratios by PCR, and genotyping and SNP analysis. Results were compared with clinical information. Results: Lactase activity and mRNA levels, and sucrase-to-lactase ratios of enzyme activity and mRNA, showed robust correlations with genotype. None of the other LCT SNPs showed as strong a correlation with enzyme or mRNA levels as did −13910. Data were consistent, with the −13910 being the causal sequence variant instead of −22018. Four individuals heterozygous for −13910T/C had allelic expression patterns similar to individuals with −13910C/C genotypes; of these, 2 showed equal LCT expression from the 2 alleles and a novel variant (−13909C>A) associated with lactase persistence. Conclusions: The identification of −13910C/C genotype is likely to predict lactase nonpersistence, consistent with prior published studies. A −13910T/T genotype will frequently, but not perfectly, predict lactase persistence in this mixed European-ancestry population; a −13910T/C genotype will not predict the phenotype. A long, rare haplotype in 2 individuals with −13910T/C genotype but equal allele-specific expression contains a novel lactase persistence allele present at −13909. Abstract : Supplemental Digital Content is available in the text